Designing transformative interventions for a world in crisis: How the ‘Worldview Journey’ invites for personal, cultural, and systems transformation - De Witt, Annick; Bootsma, Margien; Dermody, Brian J.; Rebel, Karin (Environmental science & policy, 2024)
Our world is arguably in existential crisis, with crises manifesting in nearly every facet of our existence, from education, mental health, and culture, to democracy, environment, and institutions. As our worldviews are often considered a root cause of this crisis, numerous voices emphasize the need for more transformative approaches that actively engage these deep leverage points (i.e., the places in complex systems where intervening may enable transformative, systemic change). To explore these ideas, we developed a new approach in the context of our sustainability education at Utrecht University, which we refer to as the Worldview Journey. In this article we use educational design research to present the first two phases of our intervention-design: 1) our needs analysis and problem identification, and 2) our design development and implementation, consisting of multiple iterations of conceptualizing and prototyping, while using student evaluations (n=360). Though the third phase of formal evaluation is still to be conducted, our results underscore that our intervention responds to a critical gap in current sustainability curricula (and arguably beyond) of learning to reflectively engage with diverse perspectives and worldviews, while offering an exemplary approach to address this gap. Simultaneously, our results offer a qualitative impression of students’ reception of this approach, demonstrating that 1) examining worldviews in a personal, transformative manner was greatly appreciated; 2) as was the usage of transformative learning methods; 3) with students frequently reporting small but meaningful perspective-shifts as outcome of the intervention; 4) which may thereby contribute to the development of important human, democratic capabilities. As the latter may be crucial in addressing the multiplicity of crises humanity is facing, our study arguably forges a new pathway for designing interventions that concurrently invite for personal, cultural, and systems transformation. •Design of an intervention supporting reflective engagement with diverse worldviews.•Responding to a gap in curricula while offering an exemplary approach to address it.•A qualitative impression of student evaluations (n=360) suggests that.•Examining worldviews in a personal, transformative manner was greatly appreciated.•With students reporting small but meaningful perspective-shifts as outcome.